2018
DOI: 10.1021/acs.est.7b04860
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality and Health Impacts of an Aviation Biofuel Supply Chain Using Forest Residue in the Northwestern United States

Abstract: Forest residue is a major potential feedstock for second-generation biofuel; however, little knowledge exists about the environmental impacts of the development and production of biofuel from such a feedstock. Using a high-resolution regional air quality model, we estimate the air quality impacts of a forest residue based aviation biofuel supply chain scenario in the Pacific Northwestern United States. Using two potential supply chain regions, we find that biomass and biofuel hauling activities will add <1% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Then, the air quality map layers in the above scenarios were matched with the map layer of the exposed population data. Furthermore, the health impact function is used to calculate the health benefits due to changes in pollutant concentration [28]. Since death is the most significant end point of various health effects related to PM 2.5 pollution, this paper chooses all-cause death as the end point of health effects [29,30].…”
Section: Health Impact Assessmentmentioning
confidence: 99%
“…Then, the air quality map layers in the above scenarios were matched with the map layer of the exposed population data. Furthermore, the health impact function is used to calculate the health benefits due to changes in pollutant concentration [28]. Since death is the most significant end point of various health effects related to PM 2.5 pollution, this paper chooses all-cause death as the end point of health effects [29,30].…”
Section: Health Impact Assessmentmentioning
confidence: 99%
“…Their results showed the ethanol-to-jet processing of eucalyptus residues or sugarcane residues as the most economically feasible. Contrary to studies focusing on economics, Ravi et al (2018) studied the environmental impacts of a forest residue-based BAF supply chain in the Pacific Northwest of USA. Using a regional air quality model with high-resolution, their results showed that the biorefineries can be a substantial local source of NO x and CO but regionally the increase is insignificant.…”
Section: Waste Biomassmentioning
confidence: 99%
“…However, in 2020, AIRPACT was updated with the Fire Information System with BlueSky Pipeline. The evolution of the operational AIRPACT forecast methodology is documented in the following papers (Vaughan et al, 2004;Chen et al, 2008;Herron-Thorpe et al, 2014;Ravi et al, 2018Ravi et al, , 2019 and at http://www.lar.wsu.edu/airpact.…”
Section: Airpact Descriptionmentioning
confidence: 99%